Efforts to Increase the Value of Beloso Fish (Glossogobius sp.) Into Kamaboko Products A Study of Various Proportions of Tapioca, Beloso Fish, and Mackerel (Scomboromorus guttatus Bl. Schn) - Ida Agustini Saidi; Adi Nugroho Akhmad Putra (Universitas Muhammadiyah Sidoarjo, 2010)
Beloso fish is fisheries by product which doesn’t have economic value. This study intended to raise beloso fish economic value by making them as new food product, kamaboko. The experiment used Randomized Complete Block Design (RCBD) wuth proportion of tapioca : beloso fish : spanish mackerel as treatment, comprised of eight levels and replicated three times. Those were E0 = 20% : 80%: 0%; E1= 20% : 70% : 10%; E2= 20% : 60% : 20%; E3= 40% : 60% : 0%; E4= 40% : 50% : 10%; E5= 40%: 40% : 20%; E6= 60% : 40% : 0%; E7= 60% : 30% ; 10%; E8= 60% : 20%: 20%. Variables observedwere moisture content; protein, and organoleptic test including taste, aroma, and texture. Result of theresearch showed that 20% was the appropriate tapioca proportion which gave the best product quality (low moisture content 77,38 – 78,20% and high protein 11,19 – 11,68%). Kamaboko which was used proportion of tapioca and only beloso fish(a treatment of proportion of tapioca 40% : beloso fish 60%) has higher quality than added by spanish mackerel (moisture content 78,55%; protein 11,19%; organoleptic test of taste 5,53 (like), aroma 3,67 (common) and texture 4,67 (slightly like).